Open Access Institutional Repository in the Digital Era: Preventing or Increasing Plagiarism? - Puspita, Dela; Roisah, Kholis; Lestari, Sartika Nanda (Yustisia, 2024)
The open access controversy related to the increased risk of plagiarism of scientific works at institutional repositories is the primary motivation for this research, with the aim of the study being to understand and analyze the phenomenon of open access at institutional repositories copyright infringement. This research uses a normative juridical approach or doctrinal legal research method. Implementing an open-access institutional repository system policy basically cannot eliminate the practice of plagiarism in writing scientific works in the world of education. Still, the open-access institutional repository movement can improve the ability of the general public to assess, review, differentiate, compare, and refer to scientific works. Universities in various countries implement diverse strategies to prevent plagiarism in open access institutional repositories (OAIR), such as use of plagiarism detection software, strict police and guidelines, training and education, review and evaluation process, enforcement of rules and sanctions. These approaches aim to uphold academic integrity and ensure that all publications in open repositories meet high global standards.